The Effect of Rice Husk Ash and Goat Manure on the Growth of Spinach (Amaranthus gangetius) - FS, Harahap; Hidayat, Benny (Jurnal Online Pertanian Tropik, 2021)
In the period of the last ten years increased market demand for spinach makes the outlook very promising so it is less optimal for the growth of spinach caused by the soil fertility is low so that the provision of organic material can improve soil fertility through the improvement of soil chemical to support the growth of red spinach. This study aims to determine the dosage of rice husk ash and dose of manure as well as the interaction of dosage that is optimal for the growth and yield of spinach. this research, land villa, Pasir mas which failed to compass with a height of 26 meters above sea level labuhanbatu district in August until December 2020.Research design using group factorial consisting of two factors. The first factor of rice husk ash (A) consists of 4 levels, namely : A0 = 0 ton/ha (control), A1 = 1 ton/ha equivalent to 50 g/m2 (the recommended dose), A2 = 1.5 tons/ha, equivalent to 75 g/m2. The second factor, namely the granting of goat manure (K) with three levels, namely : K0 = 0 ton/ha (control) K1 = 2 ton/ha, equivalent to 200 g/m2 (the recommended dose), K2 = 4 ton/ha, equivalent to 400 g/m2, K3 = 6 ton/ha, equivalent to 600 g/m2. The Parameters measured were plant height (cm), number of leaves (strands), Weight per Plant Sample (g). The results showed that the administration of goat manure 4 ton/ha, equivalent to 400 g/m2 can increase plant height, leaf number, and weight per plant of spinach while the provision of 1.5 ton/ha, equivalent to 75 g/m2 can increase plant height, number of leaves plant spinach